Valine: a limiting amino acid for high-producing lactating sows - Michael D Tokach; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1993)
A total of 152 lactating sows was used to determine the influence of dietary valine level on sow and litter performance. During lactation, sows were fed corn-soybean meal based diets containing .9% lysine and either .75 or .9% valine. Lactation diet had no influence on litter birth weight, pig survivability, pigs weaned per litter, or daily sow feed intake. However, sows fed the .90% valine diet had increased pig and litter weaning weights. These differences were magnified as number of pigs weaned and sow milk production increased. These results indicate that further research is needed to determine the valine requirement of the high-producing sow. However, the practical implication of this trial is that valine deficiencies limit the amount of synthetic lysine that can be used in high protein diets for the lactating sow.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Valine; Amino acids; Sows